Penerapan Sistem Pengelolaan Persediaan Terhadap Toko Happy Stationery - Ria Karina; Stanley Lo (Universitas Internasional Batam, 2021)
This community service activity (PKM) is carried out with the aim of helping one of the UMKM in Batam in designing an inventory management system that suits the needs of UMKM so that it can be applied in operational activities. The partner of this activity is the Happy Stationery Store. Previously, Happy Stationery Stores still used a handwritten manual system in recording their supplies. This made inventory recording inaccurate and inventory management, which was very large, was difficult for store managers to perform. This activity is designed to help these UMKM problems. PKM activities are carried out by interviewing, observing, and system simulation methods. Inventory management system designed based on website. The output generated from this system is in the form of main menu, inventory management list, product input list, product location tracking feature, user identification list, supplier list, customer list, and sales features. The implementation stage consists of three stages, namely the stage of introducing system features, providing system manuals, and the feedback process from the UMKM. The system has been well implemented and can provide improvements in the supply management system for UMKM.